Cross-device web search - Wu, Dan; Dong, Jing; Liang, Shaobo (Information scientist) (London : Routledge, 2022)
Cross-device Web Search is the first book to examine cross-device search behavior, which takes place when people utilize multiple devices and several sessions to research the same topic. Providing a comprehensive examination of cross-device search behaviors, the book also models and analyses their most important features and, by doing so, helps to elucidate the motivations behind such behaviors. Drawing on a variety of methods and sources, including system design, user experiments, and qualitative and quantitative analysis, the book introduces cross-device search, relates it to relevant conceptual models and identifies cross-device search topics. Providing discussion of a comprehensive range of behaviors in the context of cross-device search, including querying, gazing, clicking and touching, the book also presents the design and development of a system to support cross-device search, explores cross-device search behavior modelling and predicts users śearch performance. Cross-device Web Search will be of great interest to academics and students situated in the fields of library and information science, computer science, and management science. The book should also provide fascinating insights to practitioners and others interested in information search retrieval, information seeking behavior and human-computer interaction communities.
1. Introduction to Cross-device Search; 2. Cross-device Search Related Theories; 3. Cross-device Search Topics; 4. Cross-device Search Support Techniques and Systems; 5. Cross-device Search Behaviors; 6. Cross-device Search Behavior Modeling; 7. Discussion and Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Internet searching